2005
DOI: 10.1037/0022-0663.97.1.43
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Peer-Assisted Sentence-Combining Instruction on the Writing Performance of More and Less Skilled Young Writers.

Abstract: Mastering sentence-construction skills is essential to learning to write. Limited sentence-construction skills may hinder a writer's ability to translate ideas into text. It may also inhibit or interfere with other composing processes, as developing writers must devote considerable cognitive effort to sentence construction. The authors examined whether instruction designed to improve sentence-construction skills was beneficial for more and less skilled 4th-grade writers. In comparison with peers receiving gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 28 publications
6
124
0
4
Order By: Relevance
“…On the other hand, we expected that sentencecombining students would outperform their peers at the sentence and word levels because they learnt a strategy to write syntactically complex sentences with cohesion devices, diverse vocabulary, and modifiers. After sentence-combining instruction, non-SRSD studies have reported increases not only in the number of connectives used in writing but also in the number of sentences combined through revision (Saddler & Graham, 2005). By incorporating sentence combining into the SRSD framework, we expected extensive improvements in students' writing at the sentence-and word-levels.…”
Section: Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, we expected that sentencecombining students would outperform their peers at the sentence and word levels because they learnt a strategy to write syntactically complex sentences with cohesion devices, diverse vocabulary, and modifiers. After sentence-combining instruction, non-SRSD studies have reported increases not only in the number of connectives used in writing but also in the number of sentences combined through revision (Saddler & Graham, 2005). By incorporating sentence combining into the SRSD framework, we expected extensive improvements in students' writing at the sentence-and word-levels.…”
Section: Hypothesesmentioning
confidence: 99%
“…Planning and sentencecombining teachers completed 97% and 96% of the proposed steps, respectively. Fifth, the quality of these observed lessons was evaluated on five items: (a) level of students ' engagement, (b) students' responses to questions and participation in discussion, (c) teachers' responses to students' questions, (d) efficiency of instruction, and (e) pacing of instruction (based on Saddler & Graham, 2005). The average quality for planning and sentence-combining instruction was 3.7 and 3.6, respectively (0 = very low; 4 = very high).…”
Section: Treatment Fidelitymentioning
confidence: 99%
“…It is important to note, that some studies were placed into more than one treatment, because they included two or more treatments. For example, Saddler and Graham (2005) compared the effects of sentence-combining instruction with more traditional grammar instruction. Thus, it provided an effect size for the sentence-combining treatment as well as an effect size for grammar.…”
Section: Categorizing Studies Into Treatment Conditionsmentioning
confidence: 99%
“…In both programs, the author reported that instructors completed an average of 95% of the proposed steps. Fifth, the quality of the observed lessons was evaluated on: (a) level of students' engagement, (b) students' responses to questions and participation in discussion, (c) teachers' responses to students' questions, (d) efficiency of instruction, and (e) pacing of instruction (based on Saddler & Graham, 2005). The average quality of the self-regulation and transcription programs was 3.8 and 3.9, respectively (0 = very low; 4 = very high).…”
Section: Transcription Programmentioning
confidence: 99%